Kontribusi Dakwah Struktural dan Dakwah Kultural dalam Pembangunan Kota Palopo - Syahruddin, Syahruddin (IAIN Samarinda, 2020)
Development strategy applied in Palopo is based on the spirit of religion, local wosdom, and geographical position of the city. Such strategy is represented on the seven dimensions of Palopo’s development strategy, namely: religion, education, health/sports, traditions and culture, trade, industry, and tourism. The contribution of Da’wa towards the development of Palopo is quite significant as structural Da’wa is implemented by Municipal Government, the Ministry of Religious Affairs in Palopo, Socio-religious Organizations, and Police Department. In addition to structural da’wa, cultural da’wa is also applied by Socio-religious Organizations in cooperation with traditional-indigeous organizations in the city. The implementation of both structural and cultural da’wa has made people in Palopo love the beauty, tranquility, safety, and hospitality of their city that is built according the principle of Madinah society. There are both internal and external hinderances on the way of da’wa in Palopo. Internal obstacles consist of the diversity of Islamic school of teachings that lead to a cinflicting image of moderate vs extreme and substantial vs symbolic teachings of Islam. External onstacles, on the other side, consist of radical understandings and practices of Islamic teachings, negative impacts of information coming from social media, and globalization.Keywords: Da’wa, development, and Palopo.